The impact of ethnosectarianism on Iraqi power sharing democracy 2003-2014 - Mantki, Sangar Musheer (2017)
Since the regime was brought down by coalition forces in 2003, Iraq has been undergoing the process of democratisation through some significant political changes, namely, relatively free and competitive elections, and the freedom to form political and civil organisations. However, it faced crucial challenges that undermined this process such as ethno-sectarian violence/conflict. This thesis examines the impact of ethnic and sectarian conflict on the failure of the power sharing democracy. The thesis covers the period from 2003 until April 2014. The main themes that the thesis analyses are societal security/ethnic and sectarian violence, ethnic and sectarian inclusion, proportionality, and power devolution/federalism. For the purposes of the thesis, the societal security dilemma (SSD) theory, which focuses mainly on the roles of elites and external actors in societies that experience a power vacuum or institutional collapse in divided societies, is adopted. This theory is used for two purposes: firstly, to examine why and how the ethno-sectarian behaviour of elites affects societal security and the failure to establish a stable democracy; and secondly, to examine the viability of consociational design for the Iraqi case with the existence of distrust, fear and uncertainty among identity groups. The thesis argues that, due to fear, distrust and grievance among groups, the implementation of ethnic regions that draw lines between groups and localise the armed and security forces under a locally elected government is one of the mechanisms for reducing identity based violence and ensuring an effective power sharing democracy.